To the 60th anniversary of Professor, grand PhD in technical sciences Vadim Anatolyevich Kovtun - Palevoda Иван Иванович; Kamlyuk Андрей Николаевич; Pasovets Владимир Николаевич; Korotkevich Сергей Геннадьевич (Journal of Civil Protection, 2023)